Analisis tentang Tingkat Pendapatan Usahatani Padi dan Mendong serta Kontribusinya terhadap Pendapatan Keluarga, di Kecamatan Minggir Kabupaten Sleman Yogyakarta - Jemadi Jemadi; Siti Noor Hidayati (Jurnal Maksipreneur, 2011)
Analysis research on earnings level of rice and herb farmer business and its contribution towards family earnings in Minggir District, Sleman Regency, Yogyakarta would analyse ranging from farmer’s business characteristics, production factors earnings average towards production yield, average of earnings difference of rice farmer and grass business, and how much earnings contribution of rice/herb farmer business towards farmer family earnings.